2018
DOI: 10.1088/1674-1137/42/9/095101
|View full text |Cite
|
Sign up to set email alerts
|

Local probes strongly favor ΛCDM against power-law andRh=ctuniverse

Abstract: We constrain three cosmological models, i.e. the concordance cold dark matter plus a cosmological constant (ΛCDM) model, Power-law (PL) model, and R h = ct model using the available local probes, which includes the JLA compilation of type-Ia supernovae (SNe Ia), the direct measurement of Hubble constant (H(z)), and the baryon acoustic oscillations (BAO). For ΛCDM model, we consider two different cases, i.e. zero and non-zero spatial curvature. We find that by using the JLA alone, it is indistinguishable betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Thus, any use of BAO data, and measurements of H(z) derived from them, yields a biased outcome. Lin et al (2018) used all of the data and, not surprisingly, concluded that ΛCDM is favoured, because the standard model was assumed as the background in order to estimate the redshift space distortions. But when only the model-independent data are used (see, e.g., Melia & López-Corredoira 2017) one reaches the opposite conclusion.…”
Section: Below)mentioning
confidence: 99%
“…Thus, any use of BAO data, and measurements of H(z) derived from them, yields a biased outcome. Lin et al (2018) used all of the data and, not surprisingly, concluded that ΛCDM is favoured, because the standard model was assumed as the background in order to estimate the redshift space distortions. But when only the model-independent data are used (see, e.g., Melia & López-Corredoira 2017) one reaches the opposite conclusion.…”
Section: Below)mentioning
confidence: 99%
“…Given the still unknown nature of the current accelerated expansion, it is essential to quantify how well we can detect this phenomenon, since it could rule out the standard model, and even the possibility of the existence of the dark energy paradigm as a whole. Within the context of the standard model, cosmological observations show that the Universe is currently accelerating at roughly 5σ level (Shapiro & Turner 2006;Ishida et al 2008;Giostri et al 2012;Vargas dos Santos et al 2016;Rubin & Hayden 2016;Harisadu et al 2017;Tutusaus et al 2017;Lin et al 2018;Rubin & Heitlauf 2019), E-mail: Carlos.Bengaly@unige.ch albeit this result was recently disputed using the Hubble diagram of Type ia Supernovae (Nielsen et al 2016;Ringermacher & Mead 2016;Dam et al 2017;Colin et al 2019a;Rameez 2019;Colin et al 2019b) and quasars (Lusso et al 2019;Yang et al 2019;Velten & Gomes 2019). Other works looked at model-independent probes of cosmic acceleration, thus independent of dark energy, and even General Relativity assumptions, such as kinematic analyses (Rapetti et al 2007;Cunha & Lima 2008;Carvalho et al 2011;Lu et al 2011;Nair et al 2012;Muthukrishna & Parkinson 2016;Jesus et al 2018;Heneka 2018), besides non-parametric approaches (Mortsell & Clarkson 2009;Velten et al 2018;Harisadu et al 2018;Tutusaus et al 2019;Gómez-Valent 2019;Jesus et al 2019;Arjona & Nesseris al.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above two sets of papers, Ref. [39] showed using AIC and BIC that a combination of JLA type 1a SN sample and 30 H (z) measurements from chronometers and BAO strongly support the CDM model over R h = ct universe. They also found using AIC and BIC that the chronometer only measurements by themselves do not decisively favor any one model.…”
Section: Summary Of Bs12 Mm13 and My18mentioning
confidence: 96%
“…Although BS12 (and also Ref. [39]) has used H (z) measurements from BAO to rule out R h = ct model, we have only used the Hubble parameter data obtained from cosmic chronometers. This is due to various concerns regarding combining data from these two sources for parameter estimation within CDM and for testing R h = ct universe [2,74].…”
Section: Datasets and Analysismentioning
confidence: 99%
See 1 more Smart Citation